(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sandhigata Vata is a condition dominated by the Vata dosha, leading to both inflammatory and degenerative changes in the joints. This condition becomes especially painful when it affects mobile joints such as the knee (Janusandhi). The knee is particularly susceptible to Sandhigata Vata because it is heavily involved in daily activities and serves as a weight-bearing joint, making it more vulnerable, especially in overweight individuals. The pathogenesis of Sandhigata Vata is primarily characterized by an imbalance of Vata dosha. This study aims to evaluate the effectiveness of Janu Basti using oil for managing Sandhigata Vata.